Levels of Cortisol in CSF Are Associated With SNAP-25 and Tau Pathology but Not Amyloid-β - Wang, Qing; Zhou, Wenjun; Zhang, Jie; , The Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience, 2018)
Objective: Preclinical studies have found both hyperactivity of hypothalamic- pituitary- adrenal (HPA) axis and synaptic degeneration are involved in the pathogenesis of Alzheimer’s disease (AD). However, the data on the relationship of activity of HPA axis and synaptic degeneration in humans are limited. Methods: We compared CSF cortisol levels in 310 subjects, including 92 cognitively normal older people, 149 patients with mild cognitive impairment (MCI), and 69 patients with mild AD. Several linear and logistic regression models were conducted to investigate associations between CSF cortisol and synaptosomal-associated protein 25 (SNAP-25, reflecting synaptic degeneration) and other AD-related biomarkers. Results: We found that levels of cortisol in CSF were associated with SNAP-25 levels and tau pathologies but not amyloid-β protein. However, there were no significant differences in CSF cortisol levels among the three diagnostic groups. Conclusion: The HPA axis may play a crucial role in synaptic degeneration in AD pathogenesis.